Plan de negocio para la importación de la fruta Copoazú desde Bogotá para la producción y comercialización de vino de Copoazú en Ecuador - Gordón Mayorga, Mayra Alejandra (2018)
he main objective of this document is to identify the existence of a business opportunity to implement a product based on copoazú, which is an Amazonian fruit that has a high nutritional content and is having an important growth as a raw material for all types of products, from soaps to ice cream, this due to its versatility and easy adaptability to other components. As a main recommendation, given the existence of strong threats in the external sector, because it is an imported matter, it is necessary for the entrepreneur to have a contingency plan to deal with this type of adversity that is beyond his control. At the financial level, the initial investment needed to execute the production line and adjacent facilities is $ 74,537, which is recovered in a period of three years based on cash flows that are positive from the first year of operation. The profitability of the flows is higher than the opportunity cost and is located in a range between 25% and 29%, in the flow of the project and investor, this is favorable for the investor since it receives a higher return than the market.